Kewenangan Presiden Dalam Pengangkatan Panglima TNI Ditinjau Dari Sistem Presidensial - Arsyad, Dea (SIYASI: Jurnal Trias Politica, 2024)
Abstrack; The Presidential system ensures a strong position for the President in Indonesia's state system. However, in the derivative regulations of the 1945 Constitution, the position of the DPR (People's Consultative Assembly) is stronger than that of the President, as seen in the appointment of state officials. The Law No. 34 of 2004 regarding the Indonesian National Armed Forces (TNI) requires "approval" from the DPR in every proposal of a TNI Commander candidate submitted by the President. The involvement of the DPR in approving or disapproving has reduced the President's prerogative power. The purpose of this research is to determine the authority of the President in appointing the TNI Commander in the Presidential system, and the extent of the DPR's involvement in the appointment process. This article uses the normative juridical method with a statute approach and literature review as the research specification, with a descriptive analytical approach. The article concludes that there is a confusion in the use of the Presidential system in Indonesia regarding the appointment of state officials, as the DPR has the authority to approve candidates, which reduces the President's power in appointing the TNI Commander. This is in contradiction with the Constitution, which clearly states that Indonesia uses the Presidential system. Keyword: The President's authority, Presidential system, Appointment of TNI Abstrak: Sistem Presidensial meniscayakan posisi Presiden yang kuat dalam sistem ketatanegaraan Indonesia. Namun, dalam peraturan turunan dari UUD NRI 1945, DPR memiliki posisi yang lebih kuat jika dibanding presiden, hal tersebut terlihat dalam pengangkatan para pejabat negara. Dalam UU Nomor 34/2004 tentang TNI, mengharuskan adanya “persetujuan” DPR dalam setiap pengusulan calon Panglima TNI yang diajukan oleh Presiden. Keterlibatan DPR untuk menyetujui atau tidak menyetujui menjadikan kekuasaan prerogatif Presiden menjadi tereduksi dengan adanya ketentuan tersebut. Penelitian ini bertujuan agar dapat mengetahui bagaimana kewenangan Presiden dalam pengangkatan Panglima TNI ditinjau dari sistem Presidensial, kemudian sejauh mana keterlibatan DPR dalam pengangkatan Panglima TNI. Metode yang dipakai dalam penulisan artikel ini yaitu melalui metode pendekatan perundang-undangan (statute approach) dan kepustakaan, spesifikasi penelitian adalah deskriptif analitis. Artikel ini berkesimpulan bahwa di dalam ketatanegaraan Indonesia mengalami sebuah kerancuan dalam menggunakan sistem Presidensial terkait pengangkatan pejabat negara, DPR memiliki kewenangan untuk memberikan persetujuan yang justru mereduksi kewenangan Presiden dalam mengangkat Panglima TNI. Padahal jelas Konsititusi menyebutkan Indonesia menggunakan sistem Presidensial. Kata Kunci: Kewenangan Presiden, Sistem Presidensial, Pengangkatan Panglima TNI